2019
DOI: 10.1111/jfpp.13861
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility, physicochemical, sensorial, and nutritional characteristics of bread containing broccoli co-products

Abstract: The effects of the inclusion of industrial broccoli co‐products namely stalks and leaves into bread on physicochemical and nutritional properties were evaluated. Incorporation of powdered broccoli co‐products at a concentration of 2% (w/w) into bread formulations resulted in decreased weight and specific volumes when compared to the control (p < 0.05). Broccoli‐containing breads showed an increased green hue and a higher crust and crumb color intensity (p < 0.05). Incorporation of broccoli co‐products into bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…Broccoli florets increased levels of protein, fat, vitamin E and also antioxidant capacity in these breads. Broccoli leaves and stems have been shown to increase the phenolic content and antioxidant capacity in bread when added in a concentration of 2% (w/w), while still have an overall acceptability [81]. In addition, broccoli leaf powder has been proposed for use in gluten free sponge cake to increase the content of minerals, antioxidant capacity and protein [82], and also to increase the technological and sensory quality of gluten free sponge cake [83].…”
Section: Discussionmentioning
confidence: 99%
“…Broccoli florets increased levels of protein, fat, vitamin E and also antioxidant capacity in these breads. Broccoli leaves and stems have been shown to increase the phenolic content and antioxidant capacity in bread when added in a concentration of 2% (w/w), while still have an overall acceptability [81]. In addition, broccoli leaf powder has been proposed for use in gluten free sponge cake to increase the content of minerals, antioxidant capacity and protein [82], and also to increase the technological and sensory quality of gluten free sponge cake [83].…”
Section: Discussionmentioning
confidence: 99%
“…Texture characteristics were assessed using a TA.XT2 Texture Analyser (Stable Micro Systems Ltd., Surrey, England) connected to Exponent software v.5.0.6.0. Texture profile analysis of the breads was conducted as described by Lafarga et al (2019c) and using a P/20 aluminium compression probe. Crackers hardness was determined using a knife edge with slotted insert probe (HDP/BS) as described by Lafarga et al (2019a).…”
Section: Physical Analysismentioning
confidence: 99%
“…This is due to the reduced oxidation of lipids and protein by the bioactives present inherently in the functional ingredients and the bioactives acting as antimicrobial agents against the growth of mould [89]. Broccoli by-products from the stem and leaves were incorporated into bread and its impact on bread qualities evaluated [6]. The incorporation of 2% (w/w) of broccoli by-products consisting of stem and leaves into bread resulted in significant reduction in specific volume of 2.77 and 2.81 mL/g respectively compared to the control that recorded 2.91 mL/g.…”
Section: Fruit and Vegetable By-product Valorization In Functional Breadmentioning
confidence: 99%
“…Interestingly, no significant difference was recorded in the loaf weight of the control (48.10 g) and the broccoli stem enriched breads (47.67 g) but not for the broccoli leaf-enriched bread (49.26 g). The authors reported that the potential antimicrobial agents in the broccoli by-products impaired yeast activity, resulting in reduced leavening and a lower specific volume [6].…”
Section: Fruit and Vegetable By-product Valorization In Functional Breadmentioning
confidence: 99%
See 1 more Smart Citation